What's Old Is New Again: The Re-emergence of Yellow Fever in Brazil and Vaccine Shortages. (10th September 2018) - Chen, Lin H; Kozarsky, Phyllis E; Visser, Leo G
Abstract: Yellow fever outbreaks have continued to occur and caused infection and deaths in travelers from non-endemic regions. Yellow fever vaccine has proven effective, but vaccination decisions require balancing benefits with risks. Of concern is the continued vaccine shortage worldwide, including of the YF-VAX ® stockout in North America, which has presented many challenges. Abstract : Yellow fever outbreaks have continued and the worldwide vaccine shortage is a concern for future outbreak control. Recent outbreaks have infected travelers and caused their deaths. YF-VAX stockout in North America has serious impact on travelers and travel clinics.